Functionalized Selenium Nanotherapeutics Synergizes With Zoledronic Acid to Suppress Prostate Cancer Cell Growth Through Induction of Mitochondria-Mediated Apoptosis and Cell Cycle S Phase Arrest - An, Yulin; Zhao, Jianfu (Frontiers in Oncology, 2021)
The use of established drugs in new therapeutic applications has great potential for the treatment of cancer. Considering the advantages offered by nanomedicines (eg, cell targeting and efficient uptake), in this study, we prepared translational lentinan-functionalized selenium nanoparticles (LET-SeNPs) to treat prostate cancer (PCa). We used assays to demonstrate that a combination of LET-SeNPs and zoledronic acid (ZOL) can reduce PCa cell viability in vitro. Stability and hemocompatibility assays were used to determine the safety of LET-SeNPs and ZOL. The colocalization of LET-SeNPs was confirmed using fluorescence microscopy. JC-1 was used to measure the mitochondrial membrane potential, while the cellular uptake, cell cycle and apoptosis were estimated by flow cytometry. Finally, migration and invasion assays were used to evaluate the effects of combination treatment on cell migration and invasion. Under optimized conditions, we found that LET-SeNPs with good stability, in combination with ZOL, can effectively inhibit the metastatic PCa cells in a concentration-dependent manner, as evidenced by cytotoxicity testing, flow cytometric analysis, and mitochondria dysfunction. This enhanced anti-cancer effect may be related to the regulation of BCL2 family proteins that could result in the release of cytochrome C from the inner membranes of mitochondria into the cytosol, which is accompanied by induction of cell cycle arrest at the S phase, thus leading to irreversible DNA damage and killing of PCa cells. Collectively, the results of this study provide a new therapeutic strategy against advanced PCa and suggest the use of SeNPs and ZOL for the successful treatment of urinary tumors.